Basic systems theory for discrete linear repetitive processes using 2D Roesser model interpretations - Gałkowski, Krzysztof; Rogers, Eric; Owens, David H. (Zielona Góra: Uniwersytet Zielonogórski)
Previous work has shown that the stability conditions for discrete linear repetitive processes and 2D linear systems recursive in the positive quadrant can be tested using the same tests. This does not provide a suitable basis for studying the application of 2D linear systems theory to key, currently open, systems theoretic questions for discrete linear repetitive processes, such as e.g. what (if anything) is meant by reachability/controllability and observability and how these properties are characterised.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka